2007
DOI: 10.1016/s1571-5027(07)20014-2
|View full text |Cite
|
Sign up to set email alerts
|

Market Disintermediation and Producer Value Capture: The Case of Fair Trade Coffee in Nicaragua, Peru, and Guatemala

Abstract: Does participation in Fair Trade coffee marketing deliver added value to small-scale

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Taylor et al (2005), for example, found a significant contribution of FT in Mexico and Central America for living conditions and the emergence of governance arrangements, but also noted problems in formal structures related to communication and representation. Arnould et al (2007) compared FT coffee farmers with non‐participants in Nicaragua, Peru and Guatemala, with data showing ‘modest but measurable’ better scores on some indicators, though on others there was no difference. Moreover, Ruben et al (2009), who analysed Fairtrade and non‐Fairtrade, found that non‐Fairtrade coffee farmers had higher net household incomes in both Peru and Costa Rica, while on some other aspects, particularly organizational capacity, wealth and access to capital, Fairtrade scored better.…”
Section: Is There a ‘Best’ Standard: What Do We Know About Impact?mentioning
confidence: 99%
See 1 more Smart Citation
“…Taylor et al (2005), for example, found a significant contribution of FT in Mexico and Central America for living conditions and the emergence of governance arrangements, but also noted problems in formal structures related to communication and representation. Arnould et al (2007) compared FT coffee farmers with non‐participants in Nicaragua, Peru and Guatemala, with data showing ‘modest but measurable’ better scores on some indicators, though on others there was no difference. Moreover, Ruben et al (2009), who analysed Fairtrade and non‐Fairtrade, found that non‐Fairtrade coffee farmers had higher net household incomes in both Peru and Costa Rica, while on some other aspects, particularly organizational capacity, wealth and access to capital, Fairtrade scored better.…”
Section: Is There a ‘Best’ Standard: What Do We Know About Impact?mentioning
confidence: 99%
“… Producer groups pay a fee for certification which ranges between $2500 and $10 000 depending on size and time needed (http://www.transfairusa.org/content/resources/faq-advanced.php#fees [2 April 2010]). Being certified does not include a guarantee that producers can sell their coffee to the Fairtrade market on Fairtrade terms, and in reality most producer groups only sell part of their coffee under these conditions (see, e.g., Arnould et al , 2007; Taylor et al , 2005). Estimates based on an international source of the umbrella Fairtrade Labelling Organisations indicate that this is just 10–20%, with the rest being sold for regular market prices (Slob, 2006, p. 32).…”
mentioning
confidence: 99%
“…Cooperative societies aggregate people, resources and capital into economic units to provide opportunities for farmers to raise their productivity and income [26]. Participation in a cooperative society improves productivity by influencing a household's propensity to adopt newer farming practices and technologies via the exchange of ideas with other group members [10,[27][28][29]. Also, many studies, for instance, [30][31][32] agree that participation in cooperative societies improve the commercialisation behaviour of farmers.…”
mentioning
confidence: 99%
“…Such 'innovation networks' have always existed but have only recently been theorised as a 'new form of organisation within knowledge production for the exploration of synergies and the exploitation of complementarities ' (Pyka and Küppers, 2002) in an innovation process. Farmers may be part of larger innovation networks, but also be part of self-help approaches, such as producer organisations, which are a collective mechanism for farmers to pool resources to benefit from economies of scale and overcome challenges such as lack of technologies or credit, limited access to markets, and poor infrastructure for processing (Ton, 2008, Arnould et al, 2007, Mendoza and Thelen, 2008. Cooperatives are a specialised type of producer organisation that '…is an autonomous association of persons united voluntarily to meet their common economic, social, and cultural needs and aspirations through a jointly owned and democratically controlled enterprise' (International Co-operative Alliance, 2015).…”
Section: Introductionmentioning
confidence: 99%